Valensförbindelser, kollokationer och idiom med åt och till. Ger ordböckerna relevanta upplysningar? - Martola, Nina (LexicoNordica, 2004)
This article is a study of how three different Swedish monolingual dictionaries handle word combinations. Two of the dictionaries are definitional but with different target groups. One is for Swedish users and one is designed for learners of Swedish. The third dictionary is a dictionary of phraseology. The analyzed word combinations consist of verb phrases with the prepositions till (‘to’) and åt (‘at; for; to’) and comprise collocations, idioms and valence combinations. I compare the results of a corpus research to the contents of different dictionary entries.